AR display content in fridge - Ong, Ruby Fang Yi (2023)
As the technology of today has benefited mankind, it is important that it should be leveraged in a wide range of applications that are connected to everyday life. This project is regarding the game-changing technology trend – Augmented Reality (AR). AR is an immersive technology that involves the overlay of digital information, including text, audios, and images, onto the physical world using compatible devices such as smart glasses, smartphones, or tablets. There are four types of AR technology, which are marker-based, markerless, projection-based, and superimposition-based. In this project, marker-based AR will be integrated in the development in relation to the content of the fridge to ensure maximum functionality and usability. It is a known fact that the fridge is one of the most essential pieces of home appliances in human daily. Thus, in this project, the fridge content that will be focusing is the fruits item. The development of this project was encouraged by the need for effective assistance in educating children in basic food information learning. There are three major problems will be the focus to be solved on this project - the lack of integration of AR with fridge-related applications in pre-school education, the inability of a real-time interaction with 3D models, and the limitation of fruit’s information retrieval module. Some literature reviews and in-depth studies are carried out regarding the mentioned problems. The reviews of existing applications including Empty My Fridge, Frigloo, KitchenPal, Fridge, ARBreakfast, and HCLearn Nutrition are written in the literature review section of this report. The solution of this project is to develop a marker-based AR application that scans the fruit packaging and displays the AR virtual content. It will not only assist children in learning about the names of fruits and basic information but will indeed also replace the inefficient and uninspiring traditional textbook-based approach to education in pre-schools education. The availability of 3D models can enhance students' enthusiasm and motivation in learning. The expected final product of this project is the combination of marker-based AR technology, Unity as Integrated Development Environment (IDE), and Vuforia Engine as Software Development Kit (SDK) in an Android mobile application with the ability to display AR virtual content based on AR image markers when scanning the food packaging of fridge-related items, thus enabling a rapid retrieval module for fruit information and 3D models.